KOMPARASI REKSADANA SAHAM PERUSAHAAN INVESTASI NASIONAL DAN ASING DI INDONESIA DILIHAT DARI KINERJA, MARKET TIMING DAN STOCK SELECTION - utami, anak agung ayu putri; Sri Artini, Luh Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
The purpose of this research is to know the significance of the difference between a mutual fund company’s stock of foreign and national investment in Indonesia viewed from performance, to find out which is better between mutual fund investment company national and foreign views of market timing and stock selection. The population of this research is the mutual fund shares that are listed on the website of the financial services authority-performance outperform during periods of 2014-2016. The selection of the samples was done objectively based on investment companies. Assessment of the performance of mutual fund shares using the Sharpe Index while market timing and stock selection using Treynor Mazuy. The method used is the technique of data analysis in the form of two different test averages with the help of IBM SPSS program. The result s show ed that there was no significant difference between the mutual fund company’s stock of foreign and national investment in Indonesia viewed from the performance by using Sharpe Index, market timing stock mutual fund national invesment better than market timing foreign companies and stock selection mutual fund national invesment better than stock selection foreign companies .